2014
DOI: 10.1016/j.rpped.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidades de crianças admitidas em unidade de internação pediátrica1

Abstract: OBJECTIVE: To identify the vulnerabilities of children admitted to a pediatric inpatient unit of a university hospital. METHODS: Cross-sectional, descriptive study from April to September 2013 with36 children aged 30 days to 12 years old, admitted to medical-surgical pediatric inpatient units of a university hospital and their caregivers. Data concerning sociocultural, socioeconomic and clinical context of children and their families were collected by interview with the child caregiver and from patients, recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
1
0
1
Order By: Relevance
“…No que se refere à situação familiar, observou-se que, entre os adolescentes com câncer do Piauí, a maioria tinha seus pais casados e tinha irmãos, dados que corroboram com os dados apresentados por Benedetti et al, (2014) nos quais ao investigarem o perfil familiar dos adolescentes com câncer em uma instituição beneficente no Paraná, estes, em sua maioria, tinham seus pais possui casados e com filhos, tal como descrevem Oliveira et al (2014) em sua pesquisa, na qual mostra que os pais de crianças e adolescentes com câncer tinham, em média, de 2 a 3 filhos. Ainda no que se refere à situação familiar, o estudo mostrou que a maioria dos adolescentes residia com seus pais, indo de encontro ao que propõe o Estatuto da Criança e do Adolescente (ECA, 2017), que, conforme suas leis, recomenda aos pais que criem e eduquem seus filhos no seio da família, oferecendo-lhes segurança e proteção, sendo atribuído a eles totais responsabilidades sobre os filhos.…”
Section: Perfil Sociodemográfico Dos Adolescentes Com Câncerunclassified
“…No que se refere à situação familiar, observou-se que, entre os adolescentes com câncer do Piauí, a maioria tinha seus pais casados e tinha irmãos, dados que corroboram com os dados apresentados por Benedetti et al, (2014) nos quais ao investigarem o perfil familiar dos adolescentes com câncer em uma instituição beneficente no Paraná, estes, em sua maioria, tinham seus pais possui casados e com filhos, tal como descrevem Oliveira et al (2014) em sua pesquisa, na qual mostra que os pais de crianças e adolescentes com câncer tinham, em média, de 2 a 3 filhos. Ainda no que se refere à situação familiar, o estudo mostrou que a maioria dos adolescentes residia com seus pais, indo de encontro ao que propõe o Estatuto da Criança e do Adolescente (ECA, 2017), que, conforme suas leis, recomenda aos pais que criem e eduquem seus filhos no seio da família, oferecendo-lhes segurança e proteção, sendo atribuído a eles totais responsabilidades sobre os filhos.…”
Section: Perfil Sociodemográfico Dos Adolescentes Com Câncerunclassified
“…2,3 Day care center attendees are composed of preschoolers with a starting age of 0 to 4 years, who therefore present many vulnerabilities due to immunological immaturity and accelerated growth, and which require greater preventive care from the caregivers and teachers of the place. 4 It is still observed that children who are in day care centers get sicker than those cared for only in the home environment, due to less contact and exposure to diseases. 5,6 In the applied context, among the main systems that affect this population in day care centers are the gastrointestinal and respiratory systems, associated mainly to cases of diarrhea and various acute respiratory infections, highlighting pneumonia as the most recurrent in these cases.…”
Section: Introductionmentioning
confidence: 99%